Estado nutricional, nivel de hemoglobina y rendimiento académico en escolares - Huailla Chaupe, Maria Fernanda (2018)
This research investigation, is descriptive, cross-sectional quantitative approach, which has as its main objective to determine the relationship that exists between the nutritional indicators hemoglobin level and the academic performance in school age children in the educational institution N° 81775 "Medalla Milagrosa" of Rinconada during the year 2017. The sample was composed by 75 schools of second and third grade at the primary level. For the collection of data used a necessary instrument a register format. The results are presented in one- and double-entry statistical tables and to measure the relationship between the variables the Chi square criteria independence test was used, observing that there is a significant percentage of schoolchildren with malnutrition problems (33%), as well as that there is no statistical relationship between the study variables in the students who participated in the study.